Perceived stress, unhealthy eating behaviors, and severe obesity in low-income women. Issue 1 (December 2015) - Richardson, Andrea; Arsenault, Joanne; Cates, Sheryl; Muth, Mary
Abstract Background Stress has been associated with poor eating behaviors and diet quality, as well as high body mass index (BMI). Low-income women may be particularly vulnerable to stress and severe obesity. Yet it is unknown how stress increases the risk of severe obesity through disordered eating behaviors and poor diet quality or through mechanisms independent of diet. Methods We examined cross-sectional data from women (n = 101) with a child enrolled in the Special Supplemental Nutrition Program for Women, Infants, and Children in Cumberland County, North Carolina (spring 2012). We collected measured heights and weights to calculate BMI. Using structural equation modeling, we differentiated pathways from stress to weight status: (1) indirectly through eating behaviors (cognitive restraint, emotional eating, and uncontrolled eating) and diet quality, which we examined with the Healthy Eating Index 2010 and 24-h dietary recalls, and (2) directly through possible unmeasured risk factors independent of diet. The analysis controlled for race/ethnicity, income, age, whether the dietary recall day was typical, and whether the respondent completed one or two 24-h dietary recalls. Results Perceived stress was positively associated with uncontrolled eating (β = 0.38, p < 0.001) and emotional eating (β = 0.50, p < 0.001). However, higher stress was not associated with weight status through eating behaviors and diet quality. Independent of eating behaviors and diet quality, stress was positively associated with severe obesity (β = 0.26, p = 0.007). Conclusions Improving stress coping strategies for low-income women may improve eating behaviors and reduce severe obesity.